2008
DOI: 10.1111/j.1469-8137.2008.02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the response to nitrogen deposition inArabidopsis lyrata petraea

Abstract: Summary• The adaptive responses to atmospheric nitrogen deposition for different European accessions of Arabidopsis lyrata petraea were analysed using populations along a strong atmospheric N-deposition gradient.• Plants were exposed to three N-deposition rates, reflecting the rates at the different locations, in a full factorial design.• Differences between accessions in the response to N were found for important phenological and physiological response variables. For example, plants from lowdeposition areas h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
(85 reference statements)
2
23
0
Order By: Relevance
“…Also, considering that recovery in F v /F m is rapid (Hajek and Beckett 2008), it seems improbable that our results should be strongly inXuenced by short-term amongsite diVerences in weather conditions prior to measurements. These observations suggest that the observed results can be discussed with N deposition as the main driving factor (See also Berendse et al 2001;Bragazza et al 2004Bragazza et al , 2006Vergeer et al 2008). …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, considering that recovery in F v /F m is rapid (Hajek and Beckett 2008), it seems improbable that our results should be strongly inXuenced by short-term amongsite diVerences in weather conditions prior to measurements. These observations suggest that the observed results can be discussed with N deposition as the main driving factor (See also Berendse et al 2001;Bragazza et al 2004Bragazza et al , 2006Vergeer et al 2008). …”
Section: Discussionmentioning
confidence: 79%
“…In line with this, several authors have found indications that mosses from high N deposition sites cope better with N addition than mosses from low N deposition sites (Baxter et al 1992;Limpens and Berendse 2003;Press et al 1986). Local adaptation to regional N deposition has also recently been suggested in mosses and vascular plants (Vergeer et al 2008, Wiedermann et al 2008. However, in our study we cannot separate an adaptive response to N deposition from a physiological adjustment (e.g.…”
Section: Ecological Consequencesmentioning
confidence: 91%
“…petraea (hereafter A. l. petraea). We have published research elsewhere comparing the metabolic and growth properties of selected populations found in different regions (countries) of this distribution (Davey et al 2008, in press;Vergeer et al 2008). However, here we will focus on the variation at finer spatial scales, specifically on the variation within and between populations (sites) inside each region.…”
Section: Introductionmentioning
confidence: 99%
“…This result is supported by other studies [67,68], where M. x giganteus yields increased with increased nitrogen fertilizer in Illinois, but not across the eastern USA, where M. x giganteus was not as well adapted as in Illinois. In addition, Vergeer et al [69] reported that plant yields are more influenced by regional adaptation (e.g., flowering time and growth rate), rather than nitrogen rate. This may be why M. x giganteus yield was much less than switchgrass at 0 kg N ha −1 year −1 .…”
Section: Discussionmentioning
confidence: 99%